A complete chloroplast genome sequence of Gastrodia elata (Orchidaceae) represents high sequence variation in the species. Issue 1 (2nd January 2020) - Park, Jongsun; Suh, Youngbae; Kim, Sangtae
Abstract: Gastrodia elata is a non-photosynthetic saprophytic plant of medicinal use in the oriental countries. We report the second complete chloroplast (cp) genome of G. elata from a sample collected in Korea. The length of cp genome is only 35, 180 bp: there is no inverted repeated region and many photosynthesis genes are missing compared to typical angiosperm cp genomes. It includes 20 protein-coding genes, 3 rRNAs, and 5 tRNAs. The overall GC content of the genome was 26.7%. Relatively, high intra-specific variation (457 SNPs and 670 indels) is detected in the species comparing it with other seed plants.